Exploring Climate Change Trends in Temperature and Rainfall Across the Southeastern Coastal Area of Bangladesh - Suhan, Md Siful Islam; Adhikary, Sajal Kumar (Journal of Engineering Science, 2025)
Climate change has become a major concern for scientists all over the world. Bangladesh is considered one of the most vulnerable countries in the world to the negative impact of climate change. Particularly, the coastal part of the country faces a high risk due to the impact of climate and the frequent occurrence of natural disasters, including extreme rainfalls, waterlogging and flash flooding, cyclones, storm surges, and sea-level rise. Therefore, it is essential to explore the trends of climate change in terms of changes in rainfall and temperature in the past decades over the coastal region in Bangladesh. Hence, the aim of the current study is to assess the long-term climate change trends in monthly, seasonal, and annual temperature and rainfall caused by the impact of climate change. Four climate stations located in the southeastern coastal area in Bangladesh, including Cox’s Bazar, Teknaf, Hatiya, and Sandwip, are selected. Temperature and rainfall data are collected from the Bangladesh Meteorological Department, and 50 years of data (1950-2023) are used for the analysis. Both statistical and graphical methods are adopted for the analysis of climate change trends, in which the widely applied Mann-Kendall (MK) and Sen’s slope (SS) techniques are adopted as the statistical method, whereas the innovative trend analysis (ITA) technique is used as the graphical method. MK, SS, and ITA techniques revealed an overall increasing trend of monthly, annual, and seasonal temperature and rainfall in the study area. The results are statistically significant at the 5% significance level in most cases. Likewise, similar trends are also found in the monthly, annual, and seasonal temperature and rainfall patterns in the study area based on the ITA technique. However, seasonal rainfall trends exhibit both significant and non-significant increasing-decreasing patterns in some cases, demonstrating the most stochastic nature of rainfall in the study area. It is also important to note that MK, SS, and ITA techniques detect similar results of climate change trends in temperature and rainfall. This justifies the viability of using the user-friendly graphical ITA technique in line with the statistical MK and SS techniques for the trend analysis. Thus, it is expected that the findings of the current study could be supportive in planning for the effective climate change adaptation and management policies to address future climate change-induced disasters across the southeastern coastal area of Bangladesh. Journal of Engineering Science 15(2), 2024, 51-67